2019
DOI: 10.3390/mi10030200
|View full text |Cite
|
Sign up to set email alerts
|

Single-Sided Near-Field Wireless Power Transfer by A Three-Dimensional Coil Array

Abstract: Wirelessly powered medical microrobots are often driven or localized by magnetic resonance imaging coils, whose signal-to-noise ratio is easily affected by the power transmitter coils that supply the microrobot. A controlled single-sided wireless power transmitter can enhance the imaging quality and suppress the radiation leakage. This paper presents a new form of electromagnet which automatically cancels the magnetic field to the back lobes by replacing the traditional circular coils with a three-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…To encode the magnetic chains into the hydrogel, a main array of magnets with a set of nonrepeating codes was designed. Although Neodymium magnets usually produce strong magnetic fields, to reach more intense magnetic fields intensity in the gelation zone, two auxiliary sets of side magnets were added to the design, which are inspired from the Halbach array [19,45] . The axillary magnets are oriented such that they constructively interfere with the main array's field at top of the magnetic encoders where the gelation occurs.…”
Section: Untethered Anchoringmentioning
confidence: 99%
See 1 more Smart Citation
“…To encode the magnetic chains into the hydrogel, a main array of magnets with a set of nonrepeating codes was designed. Although Neodymium magnets usually produce strong magnetic fields, to reach more intense magnetic fields intensity in the gelation zone, two auxiliary sets of side magnets were added to the design, which are inspired from the Halbach array [19,45] . The axillary magnets are oriented such that they constructively interfere with the main array's field at top of the magnetic encoders where the gelation occurs.…”
Section: Untethered Anchoringmentioning
confidence: 99%
“…This magnetic barcoded tag must satisfy a series of conditions to interact strongly with an external stimulus. By engineering the external stimulus with arrays of permanent magnets or coils, [15,16,19,20] we are able to selectively manipulate such encoded tags from background magnetic materials via the enhanced interactions that occur with matching codes.…”
mentioning
confidence: 99%
“…Other studies have used the WPT technique at different frequencies to optimize transfer efficiency while studying side effects on skin for implantable medical devices [5]. WPT has been used in magnetic resonance imaging coils for improved magnetic field intensity on the patient side [6].…”
Section: Introductionmentioning
confidence: 99%
“…There are eight research articles and one review article published in this special issue, covering a wide range of topics: implantable sensors for detecting biophysiological and biophysical signals [1,2]; novel transducers for stimulation [3]; miniaturized antennas and biotelemetries for wireless implants [4,5,6] medical electronics and system-on-chip (SoC) [1,7]; and nano/microfabrication technologies for implantable microdevices [2,8,9]. On the device side, Chen et al reported a tongue pressure sensing platform that integrated interdigitated pressure sensing electrodes with SoC on flexible polymer films.…”
mentioning
confidence: 99%
“…This special issue includes multiple designs of wireless antennas that have been explored by different groups. In particular, Hajiaghajani et al proposed a three-dimensional coil array based on a generalized Halbach array for wireless powering of biomedical instruments within a large area of 144 cm 2 while eliminating the need for traditional magnetic shielding [4]. In another design, Fan et al designed a miniaturized circularly polarized antenna for in-body wireless communication with broadened bandwidth [5].…”
mentioning
confidence: 99%